STATE SUPPORT OF AGRICULTURE: PROBLEMS, WORLD PRACTICES AND PROSPECTS FOR UKRAINE - FURMAN, IRINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Ukraine's adaptation to the modern market system of economic activity is determined by the need to implement a number of urgent reforms aimed at increasing the role of the state in the integrated development of the economic and priority agro-industrial sector. Radical reforms of state regulation of agricultural production are necessary to overcome the existing crisis phenomena and ensure further intensive development of the agro-industrial complex. In the practice of progressive highly developed countries, the agro-industrial complex of which was formed under the influence of state regulation, demonstrates that in market conditions the efficiency of agricultural production largely depends on the level of state incentives and state support.The article examines the main aspects of state support for agriculture in modern conditions, which are regulated by regulations. The economic significance of state support is determined, its current state and main directions for agricultural enterprises are studied. The results of the analysis of preconditions and measures that led to the change of directions and volumes of state support in the budget for 2020 are presented. Ways to develop state support for the country's agricultural sector have been identified.Some world models of state support are analyzed and prospects for Ukraine are outlined. The obtained results are similar to domestic studies and defend the belief in the need for state support of the competitive environment, and not only certain forms of management and ensuring food security by means of regulatory policy coordinated to support the industry.
Keywords: agricultural sector; agricultural enterprise; farm; state support; budget; budget support; budget programs; world models of agricultural support; efficiency of state support